2022
DOI: 10.1111/joim.13462
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effectiveness and safety for low versus full dose of apixaban during extended phase oral anticoagulation in patients with venous thromboembolism

Abstract: Background The optimal dose of apixaban therapy to prevent asecondary venous thromboembolism (VTE) event remains unconfirmed. To investigate the effects of extended phase use of apixaban (2.5 vs. 5 mg twice daily) beyond 6 months of initial treatment on the risk of recurrent VTE and major bleeding events among patients with a history of VTE. Methods A retrospective cohort analysis of two large national insurance claims databases was conducted for patients diagnosed with VTE. Cox proportional hazard models afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Fourth, although current guidelines suggest the use of low‐dose anticoagulants when available, 6,54 it was not feasible to stratify the study results by apixaban dose (2.5 mg vs. 5 mg) owing to the small sample size (< 10% of apixaban users were prescribed low dose); therefore, we could not determine whether the low‐dose and the full‐dose apixaban had similar effectiveness and safety as extended treatment. However, it appeared that there were no significant differences in clinical outcomes between patients prescribed low‐dose vs. full‐dose apixaban during extended treatment 55 . Thus, our study results may not be significantly different between the two dosage groups.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Fourth, although current guidelines suggest the use of low‐dose anticoagulants when available, 6,54 it was not feasible to stratify the study results by apixaban dose (2.5 mg vs. 5 mg) owing to the small sample size (< 10% of apixaban users were prescribed low dose); therefore, we could not determine whether the low‐dose and the full‐dose apixaban had similar effectiveness and safety as extended treatment. However, it appeared that there were no significant differences in clinical outcomes between patients prescribed low‐dose vs. full‐dose apixaban during extended treatment 55 . Thus, our study results may not be significantly different between the two dosage groups.…”
Section: Discussionmentioning
confidence: 63%
“…However, it appeared that there were no significant differences in clinical outcomes between patients prescribed low-dose vs. full-dose apixaban during extended treatment. 55 Thus, our study results may not be significantly different between the two dosage groups. Fifth, owing to the lack of death information, we could not evaluate the mortality associated with extended treatment.…”
Section: Strengths and Limitationsmentioning
confidence: 62%
“…Therefore, we could not determine whether different doses had similar safety and effectiveness when administered as an extended anticoagulation therapy. A previous study did not find that the clinical outcomes differenced when comparing patients prescribed low‐dose apixaban versus those prescribed the full‐dose of apixaban during extended treatment 42 . Fourth, we had a relatively short follow‐up period, which did not enable full exploration of the long‐term effects of extended phase anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study did not find that the clinical outcomes differenced when comparing patients prescribed low‐dose apixaban versus those prescribed the full‐dose of apixaban during extended treatment. 42 Fourth, we had a relatively short follow‐up period, which did not enable full exploration of the long‐term effects of extended phase anticoagulant therapy. Last, this study is generalizable only to Medicare beneficiaries, who are older or have more comorbidities compared to an average adult population.…”
Section: Discussionmentioning
confidence: 99%
“…In Denmark, less than 5% of the patients initiated an extended treatment with 10 mg rivaroxaban or 2.5 mg apixaban which was administered twice daily after an initial treatment period of at least 3 months between 2017 and 2018 [ 45 ]. Using US claims data, DeRemer et al investigated the extended treatment with 2.5 mg vs. 5 mg apixaban among more than 6000 patients with venous thromboembolism who had completed 6 months of an initial treatment [ 46 ]. The authors concluded that 2.5 mg apixaban was associated with similar outcomes as those which were seen with the higher dose, but this study highlights limitations such as confounding by indication, given the nature of the observational study design.…”
Section: Anticoagulation For Acute and Extended Treatmentmentioning
confidence: 99%